Plan de negocio para la creación de una empresa purificadora y envasadora de agua, cantón Quevedo, año 2014 - Barreiro Bravo, Xiomara Lourdes (2015)
This project consists of the design of the business plan for the creation of a company dedicated to purify water by industrial and specialty packaging processes and make water and purified for subsequent distribution process to different sectors and / or shops Quevedo canton. The idea of creating a water bottling company arises from the need to be seen in the Quevedo canton have with a supplier that not only bottled product, but also count on a plant and machinery specializing in purification, processing and cooling water. The universe of this research is 173,575 persons representing urban and rural population of the Canton Quevedo. The choosing of the sample was performed using a simple random model, a sample of 383 respondents was obtained. The most frequently consumed beverage is bottled water; accounting for 38%; 92% reported drinking bottled water, presenting most frequently consumed is the pint, representing 74% of the total. 57% of respondents said they prefer natural water and 80% of respondents agree that a project be undertaken to produce bottled water. Bottled Water Project is financially viable, because its value NPV of US $482,458.47 indicates that the project is giving a gain greater than zero. The internal rate of return of the project is 18.6%, indicating an above benchmark rate return